Relationship between velocity reached at VO2max and time-trial performances in elite Australian rules footballers - Lorenzen, C.; Williams, M. D.; Turk, P. S.; Meehan, D. L.; Cicioni Kolsky, D. J. (International Journal of Sports Physiology and Performance, 2009)
Purpose: Running velocity reached at maximal oxygen uptake (vVO2max) can be a useful measure to prescribe training intensity for aerobic conditioning. Obtaining it in the laboratory is often not practical, and average velocities from time trials are an attractive alternative. To date, the efficacies of such practices for team sport players are unknown. This study aimed to assess the relationship between vVO2max obtained in the laboratory against two time-trial estimates (1500 m and 3200 m). Methods: During the early preseason, elite Australian Rules football players (n = 23, 22.7 ± 3.4 y, 187.7 ± 8.2 cm, 75.5 ± 9.2 kg) participated in a laboratory test on a motorized treadmill and two outdoor time trials. Results: Based on average velocity the 1500-m time-trial performance (5.01 ± 0.23 m·s-1) overestimated (0.36 m·s-1, d = 1.75), whereas the 3200-m time trial (4.47 ± 0.23 m·s-1) underestimated (0.17 m·s-1, d = 0.83) the laboratory vVO2max (4.64 ± 0.18 m·s-1). Despite these differences, both 1500-m and 3200-m time-trial performances correlated with the laboratory measure (r = -0.791; r = -0.793 respectively). Both subsequent linear regressions were of good fit and predicted the laboratory measure within ±0.12 m·s-1. Conclusion: Estimates of vVO2max should not be used interchangeably, nor should they replace the laboratory measure. When laboratory testing is not accessible for team sports players, prescription of training intensity may be more accurately estimated from linear regression based on either 1500-m or 3200-m time-trial performance than from the corresponding average velocity.